Evaluation on the Thermo-Oxidative Degradation of PET using Prodegradant Additives - Ashwinder, Chelliah; Malini, Subramaniam; Gupta, Ritu; Gupta, Arun (Informatics Publishing Limited, 2017)
Objectives: Transition metal stearates are example of potent pro-degradants reported to work at trace levels. They speed up the oxidative reaction leading to polymeric chain cleavage and reduction in molecular mass causing bio-assimilation of plastic waste. In this paper, attempt to analyze the effect of different loading amounts of cobalt stearate (CS) on the polymeric matrix of polyethylene terephthalate (PET) has been reported. Methods/Statistical Analysis: Formulated compounds were melt blended using an extruder and the extrudates were pelletized prior to molding into bone shaped specimens using an injection molding machine for characterization purpose. Findings: The effects on the incorporation of CS on the mechanical properties revealed that CS influences its tensile strength and elongation at break (%) at processing stage and studies based on Fourier Transform Infrared Spectroscopy (FTIR) spectra and carbonyl index (CI) measurements indicate that blends’ consisting of 0.25CS contributes to thermal degradation of PET. Application/Improvements: The outcome of this study would assist in the production of biodegradable materials which could decompose in shorter time frame as well as reduces plastic waste in environment.